An Advanced, Risk-Driven Sexual Health Curriculum for First-Year Internal Medicine Residents - Maria Elizabeth Maldonado; Jennifer Rusiecki (Association of American Medical Colleges, 2022)
Introduction Despite recommendations for annual chlamydia screening for young, sexually active females, chlamydia rates continue to increase nationally. Medical school students often receive limited training in obtaining comprehensive, risk-based sexual histories, leading to less screening for sexually transmitted illnesses (STIs). Consequently, many internal medicine (IM) residents feel unprepared for advanced sexual history taking and site-specific STI testing based on sexual practices. Methods We developed a case-based interactive didactic session for IM and med/peds residents. We focused on more advanced topics, such as comprehensive sexual history taking, secondary site testing for STIs, and patient counseling. Results Based on pre- and postcurriculum surveys, interns reported increases in comfort (scale: 1 = very low comfort, 5 = very high comfort) with counseling after positive STI results (Ms: pre = 2.9, post = 3.5, p < .01) and providing education on safe sex practices (Ms: pre = 3.0, post = 3.6, p < .01) and modest improvement in comfort with expedited partner therapy (EPT; Ms: pre = 2.1, post = 2.5, p = .06). An increase in self-reported confidence with collecting site-specific testing (composite Ms: pre = 2.7, post = 3.5, p < .01) was also seen. Percentage correct on knowledge questions increased from 48% to 78% postcurriculum (p = .01). Discussion This curriculum demonstrated improvement in knowledge and comfort with sexual history taking, STI screening, and counseling. Comfort also improved with EPT counseling, but not significantly, which could be addressed in future iterations of the curriculum.